Dyslexia Between Reality And Misconception - Tobbi, Saida (جامعة الوادي - University of Eloued, 2020)
لملخص : يلعب المعلم دورًا رئيسيًا في تهيئة بيئة تعليمية شاملة وناجحة تسهل وتشجع التعلم للتلاميذ الذين يعانون من عُسر القراءة، ونظرًا لأن هذه البيئة الشاملة تعتمد اعتمادًا كبيرًا على وجود معارفه ومهاراته ومواقفه، تحاول هذه الدراسة التحقيق في وعي مدرسي الطور المتوسط الجزائريين للغة الإنجليزية كلغة أجنبية. تم جمع البيانات من عينة قصدية تضم 81 مدرسًا من إكماليات باتنة وضواحيها من خلال استبيان على شبكة الإنترنت، كشفت النتائج أن الغالبية العظمى من الأساتذةالذين شملهم الاستطلاع لا يدركون عسر القراءة وتأثيره على تعلم اللغة الأجنبية. حتما ، بسبب عدم إدراكهم ، فهم يسيئون فهم التلاميذ الذين يعانون من عسر القراءة ويعتبرونهم متعلمين بطيئين وأقل من متوسطي الأداء. وبالتالي ، يوصى بأن يخضع الأساتذة للتدريب الإلزامي على عُسر القراءة، مما يتيح لهم التعامل مع احتياجات هؤلاء المتعلمين. Abstract: The teacher plays a major role in establishing a successful inclusive learning environment which facilitates and promotes learning for dyslexic pupils, Since the created inclusive environment enormously relies on the presence of his/her knowledge skills, and attitudes, the present study attempts to investigate Algerian EFL middle school teachers’ awareness of and familiarity with developmental dyslexia, A purposive sample of 81 EFL middle school teachers from Batna and its suburbs was surveyed through an online questionnaire; Findings revealed that the overwhelming majority of the surveyed respondents are not aware of developmental dyslexia and its effects on foreign language learning. Inevitably, because of their unawareness, they misconceive dyslexic pupils and consider them sluggish learners and below average performers; Thus, it is recommended that teachers undergo compulsory training on dyslexia which enables them cope with the needs of such impaired learners.
مقال
Keywords: Developmental dyslexia; awareness; familiarity; Algerian EFL middle school teachers; training